Perancangan Iklan Layanan Masyarakat Bahaya Merokok bagi Anak Usia 10-14 Tahun di Indonesia - Saifuddin Dayana; Daniar Wikan Setyanto (LPPM STIKI Malang, 2024)
Adolescence is a period marked by high curiosity and emotional instability, making young minds vulnerable to negative influences. The lack of supervision, especially from the family, can lead to a sense of freedom without understanding the boundaries that should be observed, giving rise to social phenomena related to juvenile delinquency. This research aims to design an effective public service advertisement about the dangers of smoking for children aged 10-14 years in Indonesia through digital posters. The objectives are to raise awareness, change attitudes and perceptions towards smoking, and enhance supervision in families and schools to support positive behavioral changes for the future of the nation's youth. The research method used is a qualitative method, then for data collection using documentation methods and, literature. For data analysis methods using framing analysis. The resulting public service advertisement employs a simple illustration style, which is expected to resonate well with the target audience of children and adolescents aged 10-14 years. By doing so, the audience can become more aware of the negative impacts of smoking on their growth, long-term health, and understand that it can serve as a gateway to other harmful substances abuse (NAPZA)